Knowledge, attitudes and impulses towards sexuality in adolescents in two educational institutions, Juliaca, Puno, 2014 - Mamani Luicho, Beatriz (2019)
Objective: To identify differences between the level of knowledge, attitudes and impulses towards sexuality ofteens in high school Comercio 32 and Adventist high school Tupac Amaru of Juliaca, 2014. Methods: The studyis a non experimental cutting descriptive comparative cross. The sample consisted of 188 adolescents aged 14-17years. To measure the level of knowledge a questionnaire was given about sexuality in adolescents, structured bynine closed questions which was applied to measure sexual attitudes composed of 50 items with 6 dimensions wereapplied and to measure sexual impulses test it was applied comprised of 22 items. Results: 72.3% of adolescentsof Comercio school showed 32 unaware of aspects related to sexuality, 73.1% have favorable attitudes towardsexuality; and 64.6% in the same sex drive is absent and 35.4% is present; unlike the Adventist College TupacAmaru where 62.2% of students are unaware of aspects related to sexuality, 89.7% have favorable attitudestoward sexuality; 77.6% in sex drive is absent and is present 22.4%, being higher percentages of presence inthe dimensions of masturbation, kissing and fondling by 31% and 29.3% respectively. Conclusions: There issignificant difference on sexuality in knowledge, attitudes and sexual impulses in teenagers E.I Comercio 32 thanthe Adventist high school Tupac Amaru of Juliaca. (Sig = .000).